2018
DOI: 10.1016/j.jcp.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Extrapolation-based super-convergent implicit-explicit Peer methods with A-stable implicit part

Abstract: In this paper, we extend the implicit-explicit (IMEX) methods of Peer type recently developed in [Lang, Hundsdorfer, J. Comp. Phys., 337:203-215, 2017] to a broader class of two-step methods that allow the construction of superconvergent IMEX-Peer methods with A-stable implicit part. IMEX schemes combine the necessary stability of implicit and low computational costs of explicit methods to efficiently solve systems of ordinary differential equations with both stiff and non-stiff parts included in the source … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 44 publications
0
36
0
Order By: Relevance
“…Constructing IMEX-EIS+ methods. Schneider, Lang, and Hundsdorfer [23] showed how to construct IMEX methods of the form (4) which satisfy the order conditions to order p but are error inhibiting and so produce a solution of order p + 1. In this section we show that under additional conditions we can express the exact form of the next term in error and define an associated post-processor that allow us to recover order p + 2 from a scheme that would otherwise be only pth-order accurate.…”
Section: Preliminariesmentioning
confidence: 99%
See 4 more Smart Citations
“…Constructing IMEX-EIS+ methods. Schneider, Lang, and Hundsdorfer [23] showed how to construct IMEX methods of the form (4) which satisfy the order conditions to order p but are error inhibiting and so produce a solution of order p + 1. In this section we show that under additional conditions we can express the exact form of the next term in error and define an associated post-processor that allow us to recover order p + 2 from a scheme that would otherwise be only pth-order accurate.…”
Section: Preliminariesmentioning
confidence: 99%
“…In [23] it was shown that if the truncation error vector τ n p+1 lives in the null-space of the operator D then the order of the error is of order p+1. In the following theorem we establish additional conditions on the coefficient matrices D, A F , R F , A G , R G , which allow us to determine precisely what the leading term of this error will look like and therefore remove it by post-processing.…”
Section: Preliminariesmentioning
confidence: 99%
See 3 more Smart Citations